ELECTIVITY OF ADVERBS IN VERB CONSTRUCTIONS (Лучшие интеллектуальные исследования, 2025)
Annotation: The article is devoted to the study of the systemic-semantic aspects of the compatibility of adverbs with verbs in the modern Russian language. An adverb as a part of speech plays a key role in modifying and clarifying the meanings of verbs, giving the utterance additional shades of meaning. The compatibility of adverbs with verbs is an important aspect that makes it possible to identify both the semantic structure of the language and the patterns of its functioning.